From Data to Practice: Increasing Awareness of Opioid Prescribing Data Changes Practice. Issue 3 (March 2018) - Thiels, Cornelius A.; Hanson, Kristine T.; Cima, Robert R.; Habermann, Elizabeth B.
Abstract : N/A: We hypothesized that the recent attention to the opioid epidemic, combined with internal dissemination of data on prescribing practices, impacted our institution's opioid prescribing at discharge from elective surgery. We reviewed our recent practice to assess whether this increasing awareness resulted in reductions of opioid prescriptions for patients with acute pain. Data on prescribing for patients undergoing elective surgery between 2016 and early 2017 demonstrated that opioid prescribing practices have improved in the recent era without an observed increase in refill rates. Although additional work is needed to further improve standardization and reduce opioid prescribing, these data suggest that increased awareness may be an important first step in improving opioid prescribing practices.